Development Of Halal Value Chain As A Manifestation For Economy Recovery In Post Covid-19 - Suniyyah Puspita Sari; Afni Regita Cahyani Muis; Maswati Amatillah; Nabila Thyra Janitra (Dauliyah: Journal of Islam and International Affairs, 2023)
The Covid-19 phenomenon that significantly affects the economic sector has forced all countries in the world to rise up and make recovery efforts. One of the efforts that is currently attracting attention is strengthening the halal industrial sector, which during the Covid-19 pandemic has been recognized for its success in maintaining economic stability. Halal Value Chain is a strategy used by the halal industry in an effort to recover the economy, the significance of the application of halal value chain in economic activities can give birth to a business model that can be an example for the halal industry and become a competitive advantage. This study aims to provide a comprehensive presentation on the dynamics of halal industry acceleration and halal value chain principles in the recovery of the economic sector after the Covid-19 pandemic. This research uses qualitative methods using a literature review approach from several studies. Based on research that has been carried out, it was found that the solutions offered by the halal industry through the halal value chain have proven to be one of the success factors in economic recovery after the Covid-19 pandemic, halal value chain is not just a concept that has been universally applied but is a need for the world community, because the application of the halal value chain ecosystem in the industrial sector is not only profit-oriented, however, the use of halal products and services aims to provide comfort, safety and certainty for the community. Keyword: Halal Value Chain, Halal Industry, Economy Recovery.